Variations of the social: some reflections on public health, social research and the health-society relation - Patricio Rojas (Saúde e Sociedade, 2015)
The idea of a social dimension of health is widely accepted as unavoidable and relevant for public health. This article proposes a reflection around the notion of the social examining some of the manifold ways in which it might be inherited by researchers, professionals, administrative staff and material settings involved in the practices of public health care. It will be argued that this inheritance has deep consequences for efforts of care inasmuch these different versions of the social characterise, circumscribe and reframe the health-society relation, modifying the scope under which public health issues are tackled or dismissed. To ground this seemingly abstract discussion I will work considering a specific public health problem: the case of frequent attenders in public health. Drawing on two approaches from the Sociology of Health (i.e. illness-behaviour and the user-professional relation) and the field of Science and Technology Studies, I will show how these ways of framing the study of frequent attenders assume and simultaneously promote three different versions of the social. The article aims to explore how social research in these traditions participate in the achievement and promotion of specific health-society relations, in which certain notions of the social operate helping or limiting research and care efforts by creating richer or poorer possibilities for posing, examining and facing the problems of public health.